Kepemimpinan dan Manajemen Sumber Daya Manusia di Sekolah Islam - Feby Yansasnie; Dina Damayanti; Dilla Nur Octaviana; Lukmanul Hakim (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2026)
This study aims to critically explore the concepts, characteristics, and practical implementation of Islamic leadership in the context of human resource management within Islamic educational institutions in the contemporary era. The research adopts a qualitative approach using a case study design, supported by literature review, thematic analysis, and in-depth interviews with key informants, including school leaders and administrative staff. The findings indicate that Islamic leadership emphasizes managerial and administrative roles that integrate ethical, moral, and spiritual values in managing educational institutions, which play a strategic role in shaping professional conduct and value-based organizational culture. The study also identifies several challenges in implementing human resource management in Islamic schools, particularly constraints related to limited digital literacy and the absence of sustainable professional development programs. Nevertheless, the integration of Islamic leadership values with effective human resource management practices contributes to improving teacher performance, strengthening collaborative work culture, and fostering adaptive and competitive educational environments. Therefore, this research suggests strengthening value-oriented Islamic leadership and innovative human resource management strategies through sustained institutional efforts to enhance the overall quality of Islamic education.